2016
DOI: 10.1556/034.58.2016.1-2.7
|View full text |Cite
|
Sign up to set email alerts
|

Stipe anatomical studies on selected pteridophytes of South India

Abstract: Present study is based on the stipe anatomy of 13 selected species of pteridophytes of South India. Detailed description, key to the taxa based on stipe anatomy, photographs and descriptions are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In Parahemionitis cordata, sclerenchymatous cells are arranged in 4-5 layers. while Pteris confusa and Pteris showed 2-3 layers of sclerenchymatous cells (Resmi et al 2016).. 4.E-F) located on the dorsal side. The position vascular bundle is also similar, only one vascular bundle located in the middle of dorsal side.…”
Section: Anatomical Studymentioning
confidence: 92%
“…In Parahemionitis cordata, sclerenchymatous cells are arranged in 4-5 layers. while Pteris confusa and Pteris showed 2-3 layers of sclerenchymatous cells (Resmi et al 2016).. 4.E-F) located on the dorsal side. The position vascular bundle is also similar, only one vascular bundle located in the middle of dorsal side.…”
Section: Anatomical Studymentioning
confidence: 92%
“…The study of anatomy in fern had been previously reported (Haq 2017;Kotrnon 2007;Resmi et al 2016;Talip et al 2012). In this study we examined the anatomy of the rhizome and stipe.…”
Section: Rhizomementioning
confidence: 96%
“…However, only limited studies of fern anatomy from this province had been reported on other taxa such as Dicranopteris and Nephrolepis (Sofiyanti et al 2019b), and no report was on the anatomical study of Pyrrosia from Riau Province. The study of anatomical characteristics of rhizome and stipe in ferns had been widely carried on many taxa (Nopun et al 2016;Resmi et al 2016;Sofiyanti et al 2019b;Tian et al 2014). Therefore, this study was aimed to provide the detailed morphological and anatomical characteristics of Pyrrosia from Riau Province.…”
Section: Introductionmentioning
confidence: 99%
“…Some Malaysian ferns had been examined their stipe anatomy, such as Gleicheniaceae including Dicranopteris linearis (Yen 2006), Davallia, including Davallia denticulata (Talib et al 2012), Blechnum (Talip et al 2014). While Resmi et al (2016) reported the stipe anatomy of Adiantum, Drynaria, Lygodium, Marsilea, Pityrogramma, and Pteris from South India. In this study, we examined the stipe anatomy of all fern species in this study.…”
Section: Stipe Anatomymentioning
confidence: 99%